Excavations at Hornish Point (Scottish Historical and Archaeological Internet Reports, 2003)
Details of site location and topographical survey are presented for this 50-metre length of midden deposit. A second midden was recorded nearby in 1980 and there are a number of other types of archaeological sites in the vicinity. Radiocarbon dates are exclusively Iron Age and are integrated into the archaeological description along with artefacts and ecofacts. The site was divided into two areas, the southern Area A was characterised by deeply stratified layers while Area B in the north was characterised by masonry structures. The 31 blocks within these two areas contained remains including cultivation deposits, windblown deposits, midden deposits, a wheelhouse, masonry, structural debris, a revetment wall and a blackhouse. Animal bone, fish, shellfish and bird bones including great auk were recovered. Of particular note was the presence of juvenile human remains and four processed animal carcasses in a series of pits at the base of block 18.